A bibliometric study on soft computing techniques and applications in top most populated asian countries. (2021) - Ramkumar, S.; Kartheeswaran, S.; Kesavan, M. Barath; Lavakumar, V.; Elanjiyam, G.; Thamaraiselvi, G.; Priya, B. Shanmuga
Abstract: Through this research proposal sanctioned by Department of Science and Technology (DST) NSTMIS (National Science & Technology Management Information System), Government of India, we focused to analyze the performances of soft computing techniques and its applications growth in top most populated countries from the Asian Continent through PubMed database from the year 1999 to 2019. This paper analyzes that the number of paper published in country-wise and most productive authors in the most populated countries in the Asian Continent under the soft computing techniques and its applications. The extracted data was visualized with the help of VOSviewer to analyze the data. From this study, we identified that china shows most published papers as well as most productivity authors in the field of Artificial intelligence, Pattern Recognition and Neural Networks. Few countries like Myanmar, Uzbekistan, Nepal, and Afghanistan from Asian continent showed less number of publications with limited cited articles in the soft computing fields.